Rumination in major depressive disorder is associated with impaired neural activation during conflict monitoring - Alderman, Brandon L.; Olson, Ryan L.; Bates, Marsha E.; Selby, Edward A.; Buckman, Jennifer F.; Brush, Christopher J.; Panza, Emily A.; Kranzler, Amy; Eddie, David; Shors, Tracey J. (Frontiers in Human Neuroscience, 2015)
Individuals with major depressive disorder (MDD) often ruminate about past experiences, especially those with negative content. These repetitive thoughts may interfere with cognitive processes related to attention and conflict monitoring. However, the temporal nature of these processes as reflected in event-related potentials (ERPs) has not been well described. We examined behavioral and ERP indices of conflict monitoring during a modified flanker task and the allocation of attention during an attentional blink (AB) task in 33 individuals with MDD and 36 healthy controls, and whether their behavioral performance and ERPs varied with level of rumination. N2 amplitude elicited by the flanker task was significantly reduced in participants with MDD compared to healthy controls. Level of self-reported rumination was also correlated with N2 amplitude. In contrast, P3 amplitude during the AB task was not significantly different between groups, nor was it correlated with rumination. No significant differences were found in behavioral task performance measures between groups or by rumination levels. These findings suggest that rumination in MDD is associated with select deficits in cognitive control, particularly related to conflict monitoring.